Genetics of resistance to leaf and stripe rust diseases in the spring wheat 'Amadina' - Nyori, Peter Michael Bulli (Kansas State University, 2010)
In this research, a recombinant inbred line (RIL) population derived from cross between a leaf rust- and stripe rust-susceptible spring wheat ‘Avocet S’ and a slow leaf- and stripe-rusting resistant spring wheat ‘Amadina’ was used to postulate and map leaf rust seedling resistance genes, identify quantitative trait loci (QTL) for slow-rusting resistance against leaf and stripe rust, and study slow leaf-rusting components, latent period and infection frequency. Two known Lr genes (Lr23, and Lr26) were identified to be present in ‘Amadina’ through gene postulation, pedigree, cytogenetic, and polymerase chain reaction analyses. One unknown gene associated with seedling resistance was also mapped on chromosome 1BL. In greenhouse experiment, it was estimated that at least five genes conditioning final disease severity (FS) and latent period (LP), and four genes conditioning infection frequency (IF), segregated in the population. Correlations between LP and FS, and LP and IF were moderately negative, and that between IF and FS was moderately positive, indicating inter-dependence of the traits. Two QTL on chromosomes 1BL and 6BL were associated with LP and FS, and three QTL on chromosomes 1BL, 6BL and 2DS were associated with IF. Segregation of the RIL population in field experiment indicated that there were at least four and three adult plant resistance (APR) genes involved in resistance for leaf and stripe rust. Six QTL on chromosomes 3AL, 4AL, 1BL, 5BL, and 7BL were associated with APR for leaf rust, and seven QTL on chromosome 4AL, 5AL, 1BL, 2BL, 4BL, 5BL, 2DL, and 4D were associated with APR for stripe rust. Our results indicated that the major portion of genetic variability for slow-rusting resistance was additive gene action, and, to some extent, epistasis. In this research, we also explored the utility of remote sensing and geographic information systems (GIS) and analytical operations to discriminate leaf rust pustules from other parts of leaf and to accurately determine pustule size in ‘Amadina’ and ‘Avocet S’.
Keywords: Leaf rust; Stripe rust; Wheat; Resistance; Agriculture, Agronomy (0285); Biology, Genetics (0369)